2008
DOI: 10.1021/ef8001026
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Methanol Addition to Gasoline on the Performance and Fuel Cost of a Spark Ignition Engine

Abstract: This study is concerned with investigating experimentally the effects of methanol blending to base gasoline on the performance and fuel cost of a spark ignition (SI) engine. The fuel blends were prepared by blending 5, 10, 15, and 20 vol % of methanol with a specified amount of base gasoline. These fuel blends were designated as M5, M10, M15, and M20, respectively. Base, leaded, and unleaded gasolines were also used in the study. The experiments were conducted under various engine speeds, spark timings (STs), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
24
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(29 citation statements)
references
References 18 publications
0
24
0
2
Order By: Relevance
“…The results showed that engine torque and power decreased, whereas the brake thermal efficiency improved with the increase of methanol percentage in the fuel blend. Other authors [16] have studied the influence of methanol-gasoline blends on the gasoline engine performance. The results showed that the highest brake mean effective pressure (BMEP) was obtained from 5% methanol-gasoline blend.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that engine torque and power decreased, whereas the brake thermal efficiency improved with the increase of methanol percentage in the fuel blend. Other authors [16] have studied the influence of methanol-gasoline blends on the gasoline engine performance. The results showed that the highest brake mean effective pressure (BMEP) was obtained from 5% methanol-gasoline blend.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, alcohols are the most popular additives as octane boosters and as a partially oxidized fuel in gasoline fuel. The influences of methanol, ethanol, or their mixtures with gasoline on the performance parameters, combustion characteristics and exhaust emissions of SI engines were extensively studied in the literature [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15]. In one of these studies, the effects of added methanol into gasoline on engine performance was investigated in an SI engine by Abu-Zaid et al [1].…”
Section: Introductionmentioning
confidence: 99%
“…Methanol (CH3OH) and ethanol (C2H5OH), regarded as the most attractive alternative alcohol fuels for spark ignition engine, have some similar advantages over gasoline. They have excellent combustion properties and better antiknock characteristics [7,8]; moreover, supplying same amount of energy rather than quantity as gasoline, the two alcohol fuels could not only keep and even improve the original engine power but also improve the thermal efficiency and reduce the regulated emissions of hydrocarbon (HC), carbon monoxide (CO), and oxides of nitrogen (NO,) [9][10][11][12][13][14]. However, unbumed CH3OH and C2H5OH are emitted when the engine runs on the alcohol/gasoline blends [14,15], especially the CH3OH is a toxic pollutant.…”
Section: Introductionmentioning
confidence: 99%
“…The regulated emissions characteristics of alcohol/gasoline blends fueled spark ignition engine have been adequately studied under various working conditions throughout the world [9][10][11][12][13][14][15], and the researchers have obtained a consensus that the addition of alcohol into gasoline could reduce the volumetric emission of HC, CO, and NOx pollutants. A few literatures focused on the alcohol emissions of spark ignition engine [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%